2020
DOI: 10.1002/lno.11686
|View full text |Cite
|
Sign up to set email alerts
|

Comparing microbial composition and diversity in freshwater lakes between Greenland and the Tibetan Plateau

Abstract: Greenland and the Tibetan Plateau, also known as the third pole, are both cold environments where anthropogenic activities are relatively weak. There are multitudinous lakes in both regions, especially in Greenland, where small water bodies are continuously created as glaciers retreat. It is unclear whether the community structure and community assembly mechanisms of these water bodies are consistent with those of lakes in the Tibetan Plateau that were indirectly influenced by glaciers. In addition, due to dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Several studies in this issue reinforce the profound effect that this changing balance may have on ecological function. For example, Vesterinen et al (2021) show that benthic macroinvertebrates can serve as a much poorer quality food source for higher trophic levels than their pelagic (zooplankton) counterparts, while Xing et al (2021) illustrate that benthic, sediment‐associated microbial communities have significantly greater richness and phylogenetic diversity than microbes in the water column, in both Greenland and on the Tibetan Plateau. While increases in nutrient loading with thaw (e.g., Tank et al 2020) may also critically affect aquatic systems, this aspect of changing lake function is only beginning to be investigated (Wauthy and Rautio 2020 b ).…”
Section: Changing Hydrology Of Lakes and Impacts On Biogeochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in this issue reinforce the profound effect that this changing balance may have on ecological function. For example, Vesterinen et al (2021) show that benthic macroinvertebrates can serve as a much poorer quality food source for higher trophic levels than their pelagic (zooplankton) counterparts, while Xing et al (2021) illustrate that benthic, sediment‐associated microbial communities have significantly greater richness and phylogenetic diversity than microbes in the water column, in both Greenland and on the Tibetan Plateau. While increases in nutrient loading with thaw (e.g., Tank et al 2020) may also critically affect aquatic systems, this aspect of changing lake function is only beginning to be investigated (Wauthy and Rautio 2020 b ).…”
Section: Changing Hydrology Of Lakes and Impacts On Biogeochemistrymentioning
confidence: 99%
“…Several studies cited in this review have highlighted the heterogeneity of the pan‐Arctic and caution against upscaling regional studies to the entire Arctic (e.g., Shogren et al 2021; Préskienis et al 2021; Xing et al 2021). Nevertheless, the time series measurements on major Arctic rivers initiated through the PARTNERS (Pan Arctic River Transport of Nutrients, Organic Matter, and Suspended Sediments) project and continued through Arctic‐GRO (Arctic Great Rivers Observatory) (McClelland et al 2008) have revealed several measurements and trends that do seem to hold across diverse environments, at least at the watershed outlet scale.…”
Section: Feedbacks and Scalingmentioning
confidence: 99%
“…In this work, we hypothesized that (1) climate warming may result in high variability in the composition of bacterioplankton communities in lacustrine water [51,52], while warming (constant and variable warming) may alter the metabolic functional structure of bacteria involved in nutrient cycling. (2) During the low-temperature period, temperature is the main limiting factor driving bacterial activity and, with the increase in temperature, nutrients may become the main limiting factor of microbial activity [27,53,54]. Hence, warming may stimulate the function of bacteria more strongly in colder seasons (such as spring and winter).…”
Section: Introductionmentioning
confidence: 99%